2021
DOI: 10.3390/brainsci11070913
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Early Life Stress-Affected Gut Microbiota

Abstract: Early life stress (ELS), such as neglect and maltreatment, exhibits a strong impact on the mental and brain development of children. However, it is not fully understood how ELS affects the body and behavior of children. Therefore, in this study, we performed social isolation on weaned pre-adolescent mice and investigated how ELS could affect gut microbiota and mouse behavior. Using the metagenomics approach, we detected an overall ELS-related change in the gut microbiota and identified Bacteroidales and Clostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Previous studies have reported that social isolation at preadolescent period caused the reduction of sociality in mice (Makinodan et al, 2012;Usui et al, 2021b). Here we showed that various social impairments and increased anxiety-like behaviors in ELS mice (Figures 2, 3).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Previous studies have reported that social isolation at preadolescent period caused the reduction of sociality in mice (Makinodan et al, 2012;Usui et al, 2021b). Here we showed that various social impairments and increased anxiety-like behaviors in ELS mice (Figures 2, 3).…”
Section: Discussionsupporting
confidence: 67%
“…In addition, reduced synapses and endogenous excitatory subtypes of the layer 5 pyramidal neurons were reported in the PFC of mice socially isolated for the same period (Yamamuro et al, 2018). We have also reported that social isolation during P21-53 induced the alteration of gut microbiota in mice (Usui et al, 2021b). These studies indicate that social isolation causes a lack of social experience and isolation stress, resulting in serious impacts on both PFC architecture and physical health.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Mice were housed in the barrier facilities of University of Fukui under 50% humidity and a 12:12 h light:dark cycle (8:00 to 20:00) and given free access to water and food. Social isolation-induced ELS was performed as described previously ( Usui et al, 2021b ). Briefly, the used experimental and control mice came from the litters of the same mother.…”
Section: Methodsmentioning
confidence: 99%